2014
DOI: 10.1007/s00216-014-7823-7
|View full text |Cite
|
Sign up to set email alerts
|

Analytical strategies for controlling polysorbate-based nanomicelles in fruit juice

Abstract: This study focused on the detection and quantification of organic micelle-type nanoparticles (NPs) with polysorbate components (polysorbate 20 and polysorbate 80) in their micelle shells that could be used to load biologically active compounds into fruit juice. Several advanced analytical techniques were applied in the stepwise method development strategy used. In the first phase, a system consisting of ultrahigh-performance liquid chromatography employing a size exclusion column coupled with an evaporative li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…The formed system presents a nanoscale size (~17-nm diameter) that is not altered by the presence of absence of CTZ. This is a strong indicator that the nanomicelles formed in the presence of CTZ are stable [ 38 ]. Indeed, we evaluated the size of these nanomicelles immediately after their preparation and after up to 24 hours at room temperature, and no structural alterations were detected (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…The formed system presents a nanoscale size (~17-nm diameter) that is not altered by the presence of absence of CTZ. This is a strong indicator that the nanomicelles formed in the presence of CTZ are stable [ 38 ]. Indeed, we evaluated the size of these nanomicelles immediately after their preparation and after up to 24 hours at room temperature, and no structural alterations were detected (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…The potential of DART coupled to TOF‐MS without pretreatment was verified through fast analyzing various additives including antimicrobial preservatives (benzoate, sorbic acid), artificial sweeteners (aspartame, acesulphame K), acidulants (citric acid), and non‐artificial compositions, for example, saccharides (hexose, disaccharide) and vitamins (ascorbic acid) (Cajka et al, ). The presence of polysorbate‐based nanomicelles (i.e., polysorbate 20/80, typically used in micelle shells) loading biologically active compounds (e.g., tocopherol acetate) were also confirmed by DART‐orbitrap‐MS, leading to a LCL of 1,000 µg mL −1 (Krtkova et al, ).…”
Section: Applications In Food Safety and Quality Assurancementioning
confidence: 98%
“…Six phytohormones were analyzed simultaneously using a DART ion source and single drop liquid-liquid microextraction in three different kinds of freshly prepared fruit juice in less than 30 min [183]. Another study on fruit juice using a DART ion source also demonstrated high-throughput screening and detection of polysorbate 20/80 micelles in apple juice [184]. A DART ionization source coupled with a high-resolution mass spectrometer was used for screening aflatoxins from different surfaces [185].…”
Section: Applications Of Dart-msmentioning
confidence: 99%